Development of IoT-Based Physics Practicum Module Using Physics Digital Props for Particle Dynamics Learning - Wahyudi, Muh; Hadi, Sunandar Azma'ul; Marsena, Juliana Azma'ul (Universitas Islam Negeri (UIN) Mataram, 2025)
This study aimed to develop a Physics practicum module based on Physics Digital Props (PDP) for particle dynamics learning and to examine its feasibility, practicality, and effectiveness. The research employed a Research and Development approach using the 4D model, consisting of define, design, develop, and disseminate stages. The participants were tenth-grade senior high school students involved in limited and field trials. The research instruments included expert validation sheets, student response questionnaires, and conceptual understanding tests. Data were analyzed using descriptive quantitative techniques. The results showed that the module achieved a feasibility score of 88.6% from material experts and 90.2% from media experts, both categorized as very feasible. Student responses indicated a practicality level of 89.4%, classified as very good. Furthermore, students’ conceptual understanding improved significantly, as indicated by an N-gain score of 0.72 in the high category. These findings demonstrate that the PDP-based practicum module is feasible, practical, and effective for physics learning. The novelty of this study lies in the integration of Physics Digital Props as an interactive digital practicum medium that supports experimental-based learning. The developed module is expected to serve as an innovative alternative for teaching particle dynamics and to encourage the development of technology-integrated instructional materials in physics education.